KOMUNIKASI ANTARBUDAYA MAHASISWA MALAYSIA DAN INDONESIA FAKULTAS DAKWAH DAN KOMUNIKASI UNIVERSITAS ISLAM NEGERI (UIN) SUMATERA UTARA - Insi Luthfiyah Siregar, Syukur Kholil, Mailin (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2017)
Abstract: The purpose of this study is to examine intercultural communication between Malaysian and Indonesian students at Faculty of Da'wah and Communication of State Islamic University (UIN)